2022
DOI: 10.1002/anie.202202607
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Productivity of Electrochemical CO2Reduction to Multi‐Carbon Products by Enhancing CO2Diffusion through a Porous Organic Cage

Abstract: Electroreduction of CO 2 into valuable fuels and feedstocks offers a promising way for CO 2 utilization. However, the commercialization is limited by the low productivity. Here, we report a strategy to enhance the productivity of CO 2 electroreduction by improving diffusion of CO 2 to the surface of catalysts using porous organic cages (POCs) as an additive. It was noted that the Faradaic efficiency (FE) of C2 + products could reach 76.1 % with a current density of 1.7 A cm À 2 when Cu-nanorod(nr)/CC3 (one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…Based on the obtained FE and current density, the reaction rate and turnover frequency for C 2+ products were calculated as 5639 μmol m –2 s –1 and 0.16 s –1 [ i.e., ethylene (0.056 s –1 ), ethanol (0.058 s –1 ) and acetate (0.044 s –1 )], respectively. Notably, CuBtz exhibits the highest reaction rate for yielding C 2+ products among almost all of the ECR catalysts (Table S2) except three metallic copper-based materials Cu/Fe–N–C , Cu-nr/CC3 , and F–Cu with reaction rates of ∼9380, ∼10 030, and 11 147 μmol m –2 s –1 , respectively. ,, By comprehensively considering the reaction rate, current density, and FE­(C 2+ ) (Figure e), CuBtz exhibits the highest performance for yielding C 2+ products among almost all of the coordination compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the obtained FE and current density, the reaction rate and turnover frequency for C 2+ products were calculated as 5639 μmol m –2 s –1 and 0.16 s –1 [ i.e., ethylene (0.056 s –1 ), ethanol (0.058 s –1 ) and acetate (0.044 s –1 )], respectively. Notably, CuBtz exhibits the highest reaction rate for yielding C 2+ products among almost all of the ECR catalysts (Table S2) except three metallic copper-based materials Cu/Fe–N–C , Cu-nr/CC3 , and F–Cu with reaction rates of ∼9380, ∼10 030, and 11 147 μmol m –2 s –1 , respectively. ,, By comprehensively considering the reaction rate, current density, and FE­(C 2+ ) (Figure e), CuBtz exhibits the highest performance for yielding C 2+ products among almost all of the coordination compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, CuBtz exhibits the highest reaction rate for yielding C 2+ products among almost all of the ECR catalysts (Table S2) except three metallic copper-based materials Cu/Fe−N−C, Cu-nr/CC3, and F−Cu with reaction rates of ∼9380, ∼10 030, and 11 147 μmol m −2 s −1 , respectively. 5,43,44 By comprehensively considering the reaction rate, current density, and FE(C 2+ ) (Figure 2e), CuBtz exhibits the highest performance for yielding C 2+ products among almost all of the coordination compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The reduction of CO 2 (CO 2 RR) into value-added chemicals using renewable sources provides a sustainable way for energy conversion. , For the electrochemical approach, Cu-based catalysts have drawn great attention due to their activities of converting CO 2 into multicarbon products . A major challenge is improving the selectivity of products with high industrial value such as ethylene and alcohols, from the 16 products observed during catalysis. , Recent studies on catalyst development have shown high selectivity for C ≥2 products. However, the selectivity of a particular multicarbon product on less-expensive polycrystalline Cu is relatively low. Thus, developing methods, especially the ones that are able to shift the reaction pathways between ethylene and ethanol, would be of great value for achieving highly selective CO 2 reduction systems.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical CO 2 reduction provides a promising strategy to convert CO 2 into high-value-added fuels and industrial feedstocks. , Up to now, the known products of CO 2 electroreduction include CO, HCOOH, CH 4 , C 2 H 4 , C 2 H 5 OH, etc. Compared with C 1 products, C 2+ products have higher energy density and higher market value. It is well known that great breakthrough has been made in the design and research of electroreduction catalysts to obtain hydrocarbons, but the reaction is still limited by the poor C 2+ selectivity and low activity. Among the developed and used electrocatalysts, Cu-based materials are the most promising for the synthesis of multi-carbon products in the CO 2 RR because of the moderate binding energy of the *CO intermediate, which provides favorable conditions for the C–C coupling step. However, the low selectivity and activity of C 2+ products and low current densities limit the wide application of Cu-based catalysts, which are still worthy of further study.…”
Section: Introductionmentioning
confidence: 99%